2019
DOI: 10.1007/s00018-019-03260-9
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory increase of VE-cadherin expression through ETS1 regulates endothelial barrier function in response to TNFα

Abstract: VE-cadherin plays a central role in controlling endothelial barrier function, which is transiently disrupted by proinflammatory cytokines such as tumor necrosis factor (TNFα). Here we show that human endothelial cells compensate VE-cadherin degradation in response to TNFα by inducing VE-cadherin de novo synthesis. This compensation increases adherens junction turnover but maintains surface VE-cadherin levels constant. NF-κB inhibition strongly reduced VE-cadherin expression and provoked endothelial barrier col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Surprisingly, HIF2α inhibitor had no significant effect on Ve-cadherin mRNA or total cell protein expression (Fig 4e and f) but exclusively abrogated DFO rescue of Ve-cadherin expression on the cell surface (Fig 4g). A similar phenomenon has been recently reported with TNFα and its effect on Ve-cadherin cell surface expression in HUVEC 100 . This supports our hypothesis that TNFα is involved in the mechanisms of our model.…”
Section: Discussionsupporting
confidence: 88%
“…Surprisingly, HIF2α inhibitor had no significant effect on Ve-cadherin mRNA or total cell protein expression (Fig 4e and f) but exclusively abrogated DFO rescue of Ve-cadherin expression on the cell surface (Fig 4g). A similar phenomenon has been recently reported with TNFα and its effect on Ve-cadherin cell surface expression in HUVEC 100 . This supports our hypothesis that TNFα is involved in the mechanisms of our model.…”
Section: Discussionsupporting
confidence: 88%
“…To explore the effects of MYPT1-deficient synthetic VSMCs on BBB integrity, the supernatant of human brain microvascular endothelial cells (HBVSMCs) transfected with or without Lv-shMYPT1 was collected and used to stimulate monolayer HBMECs after OGD/R. In addition to TJs, VE-cadherin plays a central role in controlling endothelial barrier function, which is transiently disrupted by proinflammatory cytokines after stroke ( Colás-Algora et al., 2020 ). Immunofluorescence staining for VE-cadherin, ZO-1, and claudin-5 showed that BBB integrity was disrupted when HBMECs were treated with the supernatant of HBVSMCs after OGD/R, which indicated that synthetic VSMCs were deleterious to BBB integrity.…”
Section: Resultsmentioning
confidence: 99%
“…Regulation of ETS1 expression in brain ECs is still unknown. To uncover the signal pathway mediating ETS1 upregulation, we analyzed the expression of Ets1 in bEND.3 cells upon stimulation of VEGFA, TNFα and TGFβ2, which can increase ETS1/Ets1 expression in human umbilical vein endothelial cells (HUVECs) or renal cells (39)(40)(41). Neither TNFα nor VEGFA could increase ETS1 expression in bEND.3 cells (Figure 2A).…”
Section: Tgfβ Increases Ets1 Expression In Brain Ecsmentioning
confidence: 99%